2012
DOI: 10.1007/s00167-012-2357-z
|View full text |Cite
|
Sign up to set email alerts
|

End-stage extension of the knee and its influence on tibial tuberosity-trochlear groove distance (TTTG) in asymptomatic volunteers

Abstract: The TTTG increases significantly at the end-stage extension of the knee. Therefore, the comparability of published TTTG values measured on radiographs, CT and MRI at various flexion/extension angles of the knee are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 21 publications
8
93
0
2
Order By: Relevance
“…However, variations in imaging modality, as well as choices in anatomic landmarks, may contribute to these varied values. Multiple studies have indicated that TTTG distances measured using MRI are approximately 2 mm less than measurements using CT, which has been attributed, in part, to a more varus position of the knee for MRI scans compared with CT. 10,18 Dietrich et al 13 recently studied 30 asymptomatic volunteers using MRI acquired at full extension and 15 Our results showed comparable findings in a study population of patients with recurrent patellar instability. We reported a 5.7-mm decrease in TTTG distance between 5 and 30 angles of knee flexion, with overall higher mean TTTG distances (17.2 AE 5.8 mm and 11.5 AE 4.9 mm at 5 and 30 , respectively), as expected in this symptomatic population.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, variations in imaging modality, as well as choices in anatomic landmarks, may contribute to these varied values. Multiple studies have indicated that TTTG distances measured using MRI are approximately 2 mm less than measurements using CT, which has been attributed, in part, to a more varus position of the knee for MRI scans compared with CT. 10,18 Dietrich et al 13 recently studied 30 asymptomatic volunteers using MRI acquired at full extension and 15 Our results showed comparable findings in a study population of patients with recurrent patellar instability. We reported a 5.7-mm decrease in TTTG distance between 5 and 30 angles of knee flexion, with overall higher mean TTTG distances (17.2 AE 5.8 mm and 11.5 AE 4.9 mm at 5 and 30 , respectively), as expected in this symptomatic population.…”
Section: Discussionsupporting
confidence: 69%
“…Diederichs et al 27 described the contribution of rotational malalignment on MRI as a factor in patellofemoral dislocation, citing greater femoral anteversion, knee rotation, and mechanical axis deviation in symptomatic patients with patellar instability when compared with asymptomatic controls. Dietrich et al 13 further speculated that the changes in TTTG distance in extension may relate to the rotational changes that occur with the screw-home mechanism. Although the exact relation between tibiofemoral rotation and changes in in TTTG distance has not yet been shown, our finding of the pattern of increased TTTG in knee extension for patients with patellar instability supports this concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the TTTG with different modalities such as MR and CT may vary, as shown by Schoettle et al [15] and Camp et al [22]. The main reason for different TTTG values within or between modalities is the technique of TTTG measurement as well as the degree of extension or flexion of the knee, as shown by Dietrich et al [23]. Determination of precise axial images for assessment of the trochlea groove as well the tibial tuberosity is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Greater medial femoral rotation may be predisposed by skeletal abnormalities such as femoral anteversion or hip muscle weakness, which was not evaluated in the present study. Another possible reason for greater medial femoral rotation could be "screw-home mechanism", which occurs at end stage of extension and knee joint locking (Wittstein et al 2009;dietrich et al 2014;Izadpanah et al 2014).…”
Section: Predictors Of Patellofemoral Pain Applying Full Weight Bearimentioning
confidence: 99%